3D interpenetrating assembly of partially oxidized MXene confined Mn–Fe bimetallic oxide for superior energy storage in ionic liquid. (20th February 2020) - Shi, Minjie; Narayanasamy, Mugilan; Yang, Cheng; Zhao, Liping; Jiang, Jintian; Angaiah, Subramania; Yan, Chao
Abstract: Owing to unique diatomic synergistic effect and electron-occupied states at Fermi level, Mn–Fe bimetallic oxides hold great promise for high-efficiency supercapacitors (SCs). However, their energy storage behaviors are exploited in the aqueous electrolytes with narrow potential window, consequently leading to the low energy density of SCs. Herein we put forward a novel electrode (Ti3 C2 TX @MFNDs) with a 3D interpenetrating assembly by confining MnFe2 O4 nanodots (MFNDs) in hierarchically layered Ti-MXene (Ti3 C2 TX ), which shows superior energy storage in high-voltage ionic liquid (IL) electrolyte. Remarkably, 3D architecture is effectively constructed by the confinement of MFNDs in partially oxidized Ti3 C2 TX with high conductivity and abundant active sites, providing multiple and continuous conductive paths for the efficient charge transport, as well as improving the structural stability of MFNDs in the electrode, demonstrated by ex-situ XRD analysis. Furthermore, the Ti3 C2 TX @MFNDs electrode exhibits a high diffusion coefficient (1.04 × 10 −8  m 2  s −1 ) and good wettability in IL electrolyte, indicating its superior IL ion dynamics. As a proof of concept, flexible ionogel SCs (FISCs) are fabricated, presenting high energy density (62.95 Wh kg −1 ), high power density, remarkable rate capability and long-term durability. Such FISCs can be also charged by harvesting sustainable energy and effectively supply power for practical applications. Graphical abstract: Image 1 Highlights: A novel electrode exhibits a 3D interpenetrating assembly. MnFe2 O4 nanodots are confined in partially oxidized Ti-MXene. High diffusion coefficient and good wettability of electrode are demonstrated. The electrode shows superior energy storage behaviors in ionic liquid electrolyte. Flexible supercapacitors with remarkable energy/power density are fabricated.